Over-Expression of Inhibitor of Differentiation 2 Attenuates Post-Infarct Cardiac Fibrosis Through Inhibition of TGF-β1/Smad3/HIF-1α/IL-11 Signaling Pathway - Lin Yin; Lin Yin; Lin Yin; Ming-xin Liu; Ming-xin Liu; Ming-xin Liu; Wei Li; Wei Li; Wei Li; Feng-yuan Wang; Feng-yuan Wang; Feng-yuan Wang; et al. (Frontiers Media S.A., 2019)
Background: Cardiac fibrosis after myocardial infarction mainly causes cardiac diastolic and systolic dysfunction, which results in fatal arrhythmias or even sudden death. Id2, a transcriptional repressor, has been shown to play an important role in the development of fibrosis in various organs, but its effects on cardiac fibrosis remain unclear. This study aimed to explore the effects of Id2 on cardiac fibrosis after myocardial infarction and its possible mechanisms.Methods: This study was performed in four experimental groups: control group, treatment group (including TGF-β1, hypoxia or MI), treatment+GFP group and treatment+Id2 group. In vitro anoxic and fibrotic models were established by subjecting CFs or NRVMs to a three-gas incubator or TGF-β1, respectively. An animal myocardial infarction model was established by ligating of the left anterior descending coronary artery followed by directly injecting of Id2 adenovirus into the myocardial infarct's marginal zone.Results: The results showed that Id2 significantly improved cardiac EF and attenuated cardiac hypertrophy. The mRNA and protein levels of α-SMA, Collagen I, Collagen III, MMP2 and TIMP1 were higher in treatment+Id2 group than those in treatment group as well as in treatment+GFP group both in vivo and in vitro. Immunofluorescence revealed that both α-SMA and vimentin were co-expressed in the treatment group and GFP group, but the co-expression were not detected in the control group and Id2 group. Additionally, our findings illustrated that Id2 had protective effects demonstrated by its ability to inhibit the TGF-β1/Smad3/HIF-1α/IL-11 signaling pathways. Besides, over-expression of Id2 reduced cardiomyocytes apoptosis.Conclusion: In conclusion, this study demonstrated that over-expression of Id2 preserved cardiac function and ameliorated adverse cardiac remodeling, which might be a promising treatment target for cardiac fibrosis and apoptosis.